The Effect of Buy Local Campaign and Consumer Ethnocentrism on Brand Love Among Indonesian Youth Consumers - Rasyid, Reizano Amri; Ratnasari, Vita; Anshori, Mohamad Yusak (Journal of Ecohumanism, 2024)
Consumer preference for local brands is increasing, especially among Generations Y and Z, who view local products as symbols of cultural identity and national pride. This study explores the influence of Buy Local Campaign (BLC) and Customer Ethnocentrism (CETH) on Brand Love (BL), with Attitude Toward Brand (ATB) as a mediator, using the Stimulus-Organism-Response (SOR) theory approach. Data were collected through an online survey from 250 respondents in Surabaya, evenly divided between Generations Y and Z, with experience purchasing local fashion brands through e-commerce platforms such as Shopee and Tokopedia. The results show that BLC and CETH significantly influence ATB, the main link to BL for both generations. However, there is an interesting difference between Generation Y and Z; in Generation Z, CETH also directly influences BL, while Generation Y requires mediation through ATB. These findings highlight the importance of building data-driven marketing strategies and generational segmentation to maximize consumer emotional loyalty to local brands. This study makes a theoretical contribution by extending the application of the SOR model to the context of local brand preferences in developing countries. It offers practical implications for developing more effective marketing campaigns. The article recommends different strategies for each generation: Generation Y requires logical and functional narratives, while Generation Z is more responsive to emotional and cultural approaches. This research supports initiatives such as the National Movement Proud of Indonesian Products (Gernas BBI) as a strategic step to strengthen the competitiveness of local brands.